Adaptive Backstepping Self-balancing Control of a Two-wheel Electric Scooter. (13th October 2014) - Son, Nguyen Ngoc; Anh, Ho Pham Huy
This paper introduces an adaptive backstepping control law for a two-wheel electric scooter (eScooter) with a nonlinear uncertain model. Adaptive backstepping control is integrated with feedback control that satisfies Lyapunov stability. By using the recursive structure to find the controlled function and estimate uncertain parameters, an adaptive backstepping method allows us to build a feedback control law that efficiently controls a self-balancing controller of the eScooter. Additionally, a controller area network (CAN bus) with high reliability is applied for communicating between the modules of the eScooter. Simulation and experimental results demonstrate the robustness and good performance of the proposed adaptive backstepping control.